The Impact of Information Attacks on The Upbringing of The Younger Generation - Закирова Мухайё Камалхановна (Web of Journals Publishing, 2023)
This article highlights the impact of information attacks on the upbringing of the younger generation in the context of globalization.
Keywords: Internet, ICT, education, education.